DEVELOPMENT DEVELOPMENT OF SCIENCE LEARNING MATERIAL BY INTEGRATING NEW LITERACY ON MOTION IN DAILY LIFE THEME FOR GRADE VIII STUDENTS - Dinda Safitri; Asrizal Asrizal; Yurnetti Yurnetti (Department of Science Education, 2020)
The 21st century education requires graduates who are broad-minded and have literacy. New literacy skills are needed by students to face the challenges of the 21st century. Science learning in the 2013 curriculum is carried out in an integrated manner. But the facts on the ground showed that science learning has not been implemented well, the unavailability of integrated science teaching materials, and student learning outcomes were still low. The solution to overcome this problem was to develop new literacy science integrated learning material. This study aims to determine the validity and practicality of using new integrated literacy science learning material. This type of research was Research and Development. The object of research was integrated science learning material for new literacy themes of motion in life. The data source were the result of the validity and practicality test. The instruments used were validation questionnaire sheets and practicality questionnaire sheets. The results show that the new integrated literacy science teaching materials are valid with a value of 79.65 and the use of new integrated literacy science teaching materials is very practical according to teachers and students with grades of 86.39 and 83.44, respectively.